2021
DOI: 10.1002/asia.202100641
|View full text |Cite
|
Sign up to set email alerts
|

Histidine Tautomerism Driving Human Islet Amyloid Polypeptide Aggregation in the Early Stages of Diabetes Mellitus Progression: Insight at the Atomistic Level

Abstract: Early oligomerization of human islet amyloid polypeptide (hIAPP), which is accountable for β‐cell death, has been implicated in the progression of type 2 diabetes mellitus. Some researches have shown the connection between hIAPP and Alzheimer's disease as well. However, the mechanism of peptide accumulation and associated cytotoxicity remains unclear. Due to the unique properties and significant role of histidine in protein sequences, here for the first time, the tautomeric effect of histidine at the early sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…[36] The results of the study indicate that the δ isomer and δδ/δɛ dimer configurations exhibit a greater degree of significance when compared to the ɛ and ɛɛ conformations. [37] The results show that the protein structure rearrangement during aggregation can affect the population and dynamics of toxic oligomerized species. [38] Although previous research has shown that the tautomeric behavior of histidine can rapidly promote oligomer aggregation, [39] the specific histidine behaviors of hIAPP, including tautomerism and protonation, remain poorly understood.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[36] The results of the study indicate that the δ isomer and δδ/δɛ dimer configurations exhibit a greater degree of significance when compared to the ɛ and ɛɛ conformations. [37] The results show that the protein structure rearrangement during aggregation can affect the population and dynamics of toxic oligomerized species. [38] Although previous research has shown that the tautomeric behavior of histidine can rapidly promote oligomer aggregation, [39] the specific histidine behaviors of hIAPP, including tautomerism and protonation, remain poorly understood.…”
Section: Introductionmentioning
confidence: 94%
“…Studies on artificial rat islet amyloid polypeptide (rIAPP) have indicated that H18 plays a crucial role in regulating hIAPP fibril formation [36] . The results of the study indicate that the δ isomer and δδ/δϵ dimer configurations exhibit a greater degree of significance when compared to the ϵ and ϵϵ conformations [37] . The results show that the protein structure rearrangement during aggregation can affect the population and dynamics of toxic oligomerized species [38] .…”
Section: Introductionmentioning
confidence: 96%
“…10 Recently, a novel histidine tautomerism/protonation hypothesis accounting for the pathogenesis of AD and other neurological diseases has been suggested by our research team. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We have demonstrated that different protonated states in the histidine imidazole ring are related to the conformational characteristics of diverse misfolded peptides (namely Ab, tau, amylin, and prion) and can influence fibrillization processes in polypeptides, resulting in proteopathies. This histidine hypothesis implies that protein accumulation may occur inherently rather than as a consequence of extrinsic agents.…”
Section: Introductionmentioning
confidence: 99%